Extensive malignant melanoma of the oral cavity: a rare occurrence - Pradeep Pradhan; Amit Kumar Adhya (University of São Paulo, 2021)
Primary malignant melanoma of the oral cavity is a rare tumor in clinical practice. Extensive malignant melanomas are still very rare in the literature. Patients with malignant melanoma of oral cavity are often diagnosed at the advanced stage of the disease due to their painless and nonspecific radiological findings. Histopathology is the gold standard for the final diagnosis and staging of the tumor. Surgery followed by radiotherapy is the standard treatment offered to patients with malignant melanoma. Here we present a rare case of extensive malignant melanoma of oral cavity which was successfully managed by surgical excision followed by adjuvant radiotherapy.